1992
DOI: 10.1080/17450399209432988
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Contamination with Separate Mycotoxins (Aflatoxins, Ochratoxin A, Citrinin, Patulin, Penicillic Acid or Sterigmatocystin) on the in Vitro Dry Matter and Organic Matter Digestibilities of Some Roughages (Berseem Hay and Wheat Straw)

Abstract: In vitro study on berseem hay and wheat straw was undertaken to investigate the the effect of mycotoxin contamination on dry matter and organic matter digestibilities. The data revealed a negative effect of most studied mycotoxins on the materials digestibility. Among the investigated mycotoxins, penicillic acid with its two concentrations (5 and 10 nmol) was the most negative, affecting digestibilities of both feed materials. Wheat straw digestibility was more influenced than berseem hay by the ochratoxin A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…paratuberculosis had higher intestinal bacterial counts than did infected hamsters that had been treated with AFB 1 . These results are substantiated by the study of Abdelhamid et al who found that effects of AFB 1 on rumen fermentation may be like antibiotics: Affecting the harmful flora and encouraging the rumen microflora as noted by slight improvements regarding in vitro rumen fermentation of wheat straw and berseem ( Trifolium alexandrinum ) hay after dietary AFB 1 exposure [ 125 ]. In this regard, fermentation patterns of Saccharomyces cerevisiae , and several Lactobacillus spp.…”
Section: Effects Of Aflatoxin B 1 On Gastrointementioning
confidence: 80%
“…paratuberculosis had higher intestinal bacterial counts than did infected hamsters that had been treated with AFB 1 . These results are substantiated by the study of Abdelhamid et al who found that effects of AFB 1 on rumen fermentation may be like antibiotics: Affecting the harmful flora and encouraging the rumen microflora as noted by slight improvements regarding in vitro rumen fermentation of wheat straw and berseem ( Trifolium alexandrinum ) hay after dietary AFB 1 exposure [ 125 ]. In this regard, fermentation patterns of Saccharomyces cerevisiae , and several Lactobacillus spp.…”
Section: Effects Of Aflatoxin B 1 On Gastrointementioning
confidence: 80%
“…However, other studies found no ( in vivo , [10]) or only slight indications ( in vitro , [121]) for a negative influence of OTA on digestibility. Using four toxin concentrations of 5.0, 20.0, 200 and 1,400 μg/L of incubation medium, a significant decrease of in vitro digestibility was found only at the highest concentration [122].…”
Section: Degradation Of Ochratoxin a In Ruminantsmentioning
confidence: 99%
“…An influence on digestibility as stated in some studies [ 11 ] may be best explained to be a result of the diarrhea induced by the mycotoxin and not by significant direct negative effects on microbes. However, other studies found no ( in vivo , [ 10 ]) or only slight indications ( in vitro , [ 121 ]) for a negative influence of OTA on digestibility. Using four toxin concentrations of 5.0, 20.0, 200 and 1,400 μg/L of incubation medium, a significant decrease of in vitro digestibility was found only at the highest concentration [ 122 ].…”
Section: Degradation Of Ochratoxin a In Ruminantsmentioning
confidence: 99%
“…Food conversion ratio did not differ among treatments, being 3.24, 3.51, 3.51, 3.40, 3.91, and 3.57 for T1, T2, T3, T4, T5, and T6, respectively; yet, the best was T1 and the worst was T5. Abdelhamid et al (1992a) found that mycotoxin contamination, particularly with OTA, negatively affect nutrients digestibility. Moreover, Abdelhamid et al (2005) reported decreased body weight gain, food intake and conversion, and nutrients digestibility.…”
Section: Food Conversion Ratiomentioning
confidence: 99%